Highly efficient fluorescent blue materials and their applications for top‐emission OLEDs. Issue 3 (16th April 2018) - Masuda, Tetsuya; Nakano, Yuki; Takahashi, Yoshiaki; Ito, Hirokatsu; Okinaka, Keiji; Kambe, Emiko; Kawamura, Yuichiro; Kuma, Hitoshi
Abstract: We developed new fluorescent blue dopants (BDs) for achieving high‐efficient blue organic light‐emitting diode. A new BD showed both high photoluminescent quantum yield >0.9 and highly horizontal orientation (S′ > 0.9) in doped film with keeping a chemical stability by introducing suitable substituents. We developed hole transporting materials and optimized the combination of hole transporting layers to decrease a carrier accumulation at the interface between electron blocking layer and emission layer. We found that the external quantum efficiency dependency from low to high current density was turned flat by promoting hole injection into emission layer. The top‐emission organic light‐emitting diode using the new BD and the optimized device architecture exhibited high efficiency of L/J/CIEy around 200 at CIEy = 0.043. Abstract : We developed new fluorescent blue dopants (BDs). A new BD showed both high photoluminescent quantum yield > 0.9 and highly horizontal orientation (S' > 0.9) in doped film. The top‐emission organic light‐emitting diode using the new BD and the optimized device architecture exhibited high efficiency of L/J/CIEy around 200 at CIEy = 0.043.